Limitele jurnalismului cetățenesc - Precup, Angela (Symbolon, 2020)
Citizen Journalism and Its Limits Citizen journalism is the practice by which people with no journalistic background act as citizen-reporters, collecting and disseminating informative contents, with the use of three basic instruments: a mobile phone, a ’good eye‘ and an internet connection. This practice does not follow journalistic principles such as validating the information or protecting the rights of the people involved, although it usually has constructive purposes, by which it attracts growing audiences. Since the citizen journalism becomes a growing source of information, even for the mass-media, its integration in the general informative circuit might be supported by the Romanian educational system, by promoting the fundamental aspects necessary for the correct practice of this type of journalism.